How Scandinavian was the early Viking Age in the Northern Isles? - Griffiths, D (Aarhus University Press, 2020)
The Northern Isles of Scotland (Orkney and Shetland) are celebrated not only as the nearest parts of the British Isles to Scandinavia, but also as their most Scandinavian in culture and heritage. The two neighbouring North Atlantic archipelagos (Fig. 1) were the last substantive territorial additions to Scotland when, as the surviving insular parts of the Norse Earldom of Orkney, they were impignorated from the Danish to the Scottish crowns in 1468-1472. Their Medieval and post-Medieval vernacular was Norn, a derivative of the Old Norse group of languages, and their landscapes abound with place-names of Scandinavian origin. Traditions of local assembly,...